A spatial equity analysis of a public health intervention: a case study of an outdoor walking group provider within local authorities in England. Issue 1 (December 2015) - Hanson, Sarah; Jones, Andy
Abstract Introduction If an intervention is not well spatially targeted, appropriate levels of uptake, efficacy, long-term compliance and improved health outcomes are unlikely to be attained. Effective health interventions should seek to achieve not only absolute improvements in health but also to reduce inequity. There is often a disparity whereby preventative interventions are more likely to be successful amongst the more affluent, a process which has been coined the 'inverse prevention law'. Physical inactivity is known to be socially patterned and disproportionately prevalent in disadvantaged communities yet there is a lack of clear evidence on which interventions have the potential to influence inequity. Walking groups have been found to have multiple health benefits and increase physical activity. In England the major facilitator is a not for profit organisation which has 70, 000 regular walkers and is lay led with 10, 000 volunteers. The aim of this study was to evaluate the extent to which walking groups operated in those places with the greatest health need and whether consequently the scheme has the potential to influence health inequity. Method The work used a spatial approach whereby geographical variations in walking group provision within the 326 local authorities in England (mean population 163, 410) were linked to health and socio-economic measures of population need. Results Generally, greater need was not associated with higher provision of the walking group intervention. Although the magnitude of differences was small, provision of the intervention tended to be poorest in those local authorities with the greatest health need, as measured by our indicators. Conclusions Without targeting those areas with greater health and socio-economic need, there is a concern that walking groups may not be set up in areas that need them most. There is therefore a potential that this intervention could, albeit in a small way, widen inequity between local authorities. However small-scale and well-intentioned, interventions need to be evaluated for their potential impact on inequity.